Copper-based metal organic framework material as well as preparation method and application thereof

By adopting a copper-based metal organic framework material with a honeycomb spherical morphology, it is used to electrocatalyze the reduction of carbon dioxide to make ethylene reaction, and the problems of low selectivity, low activity and poor stability of existing copper-based catalysts are solved, and efficient and stable ethylene preparation is achieved.

CN119613742AActive Publication Date: 2025-03-14CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311177189.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-12
Publication Date
2025-03-14
Estimated Expiration
2043-09-12

AI Technical Summary

Technical Problem

The existing copper-based catalysts have problems of low selectivity, low activity and poor stability in the carbon dioxide reduction reaction, which limits the application of electrocatalytic reduction of carbon dioxide.

Method used

A copper-based metal organic framework material has a honeycomb spherical morphology and a two-dimensional nanolayer interwoven structure. This material is prepared by hydrothermal method for electrocatalytic reduction of carbon dioxide to ethylene reaction.

Benefits of technology

It improves catalytic activity and stability, achieves high ethylene Faraday efficiency, simplifies the preparation process, reduces costs, and has good application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613742A_ABST
    Figure CN119613742A_ABST
Patent Text Reader

Abstract

The invention relates to the field of preparation of metal organic framework materials, and discloses a copper-based metal organic framework material as well as a preparation method and application thereof. The invention discloses a copper-based metal organic framework material. The metal organic framework material has a honeycomb spherical shape; the metal element in the metal organic framework material is copper; an organic ligand in the metal organic framework material is trimesic acid; wherein the diameter of the metal organic framework material spherical particles is 0.8-8 microns. The copper-based metal organic framework material disclosed by the invention is applied to a reaction for preparing ethylene by electrocatalytic reduction of carbon dioxide, and has relatively high ethylene Faraday efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of metal organic framework material preparation, and in particular to a copper-based metal organic framework material and a preparation method and application thereof. Background Art

[0002] At present, the development of human industrial civilization has led to excessive emissions of greenhouse gas carbon dioxide, which ultimately led to a series of environmental problems. Global warming, ocean acidification, melting of polar glaciers, and rising sea levels are all related to excessive carbon dioxide emissions. The atmospheric carbon dioxide content increased from 280ppm before the industrial revolution to 421ppm in 2022. Therefore, the problem of carbon emissions has become a focus of increasing attention. Electrocatalytic carbon dioxide reduction technology (reducing carbon dioxide to fuels or chemicals such as carbon monoxide, formic acid, methane, ethylene, ethanol, acetic acid and n-propanol) reduces the carbon dioxide content and converts it for utilization to achieve carbon cycle. Among them, ethylene has both high energy density and market value and is an important chemical raw material. Carbon dioxide reduction to ethylene has good application prospects, but the carbon dioxide reduction to ethylene pathway involves CC coupling and multi-electron and proton transfer. The current catalysts still face the shortcomings of low catalytic activity, low selectivity and poor stability.

[0003] Metal-based materials are the most common catalysts for electrocatalytic reduction of carbon dioxide, among which copper-based materials are the most suitable metal materials for producing multi-carbon components such as ethylene and ethanol. However, due to the constraints of CC coupling, multi-electron and proton transfer, competitive hydrogen evolution reaction and other factors, copper-based catalysts at this stage face problems such as low selectivity, low activity and poor stability, which seriously restrict the practical application of carbon dioxide reduction technology.

[0004] Metal-organic framework materials are network structures formed by self-assembly of metal nodes and organic ligands. They have rich pore structures and high specific surface area, which greatly promote the exposure of active sites. Organic ligands have the ability to regulate the electronic structure of metal active sites and further adjust the adsorption strength of reaction intermediates. The easily regulated coordination environment (such as the distance between metal sites, the number and type of ligands) promotes the selective regulation of different carbon dioxide reduction products.

[0005] In 1990, Ian D. Williams et al. (DOI:10.1126 / science.283.5405.1148) prepared Cu-BTC for the first time, with a pore size of about 1 nm and a specific surface area of ​​about 917.6 m 2 / g, Cu-O4 coordination, Cu-Cu spacing of 0.2682nm, a paddle-shaped Cu dimer structure.

[0006] In 2018, Edward H. Sargent et al. (DOI: 10.1021 / jacs.8b06407) distorted the Cu-BTC copper dimer by heat treatment to form a local asymmetric atomic structure and unsaturated coordination active sites, thereby increasing the Faraday efficiency of ethylene from 16% to 45%.

[0007] In 2021, Wolfgang Schuhmann et al. (DOI: 10.1002 / anie.202108313) used Cu-BTC carbonization to derive the CuxOyCz catalyst, added a certain proportion of polytetrafluoroethylene to adjust the hydrophobicity, reduce the electrode wetting effect, reduce the hydrogen evolution activity and increase the concentration of intermediates on the electrode surface, and the ethylene Faraday efficiency could reach 36%.

[0008] In 2021, Liqiang Mai et al. (DOI: 10.1002 / anie.202112116) prepared defective Cu-BTC, the structural unit of which was a Cu-O3-coordinated wheel-pulp-shaped Cu dimer. The low-coordination active site greatly improved the selectivity of the product hydrocarbon components, among which the Faraday efficiency of ethylene was less than 35%.

[0009] However, the existing Cu-BTC is a micron-sized octahedral block with a pore size of about 1 nm, which is not conducive to the full exposure of active sites and weakens the mass transfer efficiency. Although copper-based metal organic framework materials have a unique property of producing multi-carbon products such as ethylene and ethanol because of their suitable adsorption strength for carbon dioxide reduction reaction intermediates, the selectivity of copper-based metal organic framework materials for single products is not high due to the limitation of their inherent linear relationship of adsorption energy. Secondly, under the electrocatalytic reduction of carbon dioxide reduction potential, copper-based metal organic framework materials all show poor stability. These shortcomings have greatly limited the application of electrocatalytic reduction of carbon dioxide.

[0010] Therefore, there is an urgent need to develop a new copper-based metal-organic framework material to improve its application performance in the electrocatalytic reduction of carbon dioxide. Summary of the invention

[0011] The purpose of the present invention is to overcome the problems existing in the prior art and provide a copper-based metal organic framework material and its preparation method and application. The copper-based metal organic framework material of the present invention is used for the electrocatalytic reduction of carbon dioxide to produce ethylene, and has a high ethylene Faraday efficiency.

[0012] In order to achieve the above-mentioned object, the present invention provides a copper-based metal organic framework material on one hand, wherein the metal organic framework material has a honeycomb spherical morphology;

[0013] The metal element in the metal organic framework material is copper;

[0014] The organic ligand in the metal organic framework material is trimesic acid;

[0015] Among them, the diameter of the spherical particles of the metal organic framework material is 0.8-8 microns.

[0016] Preferably, according to X-ray diffraction characterization, the metal organic framework material has characteristic peaks at 2θ of 8.3°±0.2° and 17.0°±0.2°.

[0017] A second aspect of the present invention provides a method for preparing a copper-based metal organic framework material, the method comprising the following steps:

[0018] (1) mixing a methanol solution of a copper precursor with a methanol solution of trimesic acid to obtain a mixed solution; placing the mixed solution in a reaction container under a sealed condition to perform a hydrothermal reaction to obtain a solid product;

[0019] (2) washing and drying the solid product;

[0020] Wherein, the volume of the mixed solution is 18-50% of the volume of the reaction container;

[0021] The concentration of the copper precursor methanol solution is 40-100 mg / mL;

[0022] The concentration of the methanol solution of trimesic acid is 18-50 mg / mL.

[0023] The third aspect of the present invention provides an application of the copper-based metal organic framework material described in the first aspect or the copper-based metal organic framework material prepared by the preparation method described in the second aspect in the electrocatalytic reduction of carbon dioxide to produce ethylene.

[0024] Through the above technical solution, the beneficial effects of the present invention include:

[0025] The copper-based metal organic framework material of the present invention has a special honeycomb spherical morphology with the advantages of two-dimensional nanolayers and three-dimensional multi-level pores, and has a smaller size, which can improve mass transfer efficiency and greatly improve its catalytic activity. The copper-based metal organic framework material of the present invention is applied to the electrocatalytic reduction of carbon dioxide to ethylene reaction, has excellent stability and high ethylene selectivity, and can be used as an efficient catalyst for the electrocatalytic reduction of carbon dioxide to ethylene.

[0026] The preparation method provided by the present invention prepares the copper-based metal organic framework material with a honeycomb spherical morphology of the present invention by a simple one-step hydrothermal method. The preparation process avoids the complex process of adding additional structure regulators or sacrificial template agents commonly seen in existing preparation methods. The operation is simple, the preparation conditions are mild, the cost is low, the synthesis method is efficient, and it is easy to scale up, and it has good application advantages and prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 is a scanning electron microscope image of the copper-based metal organic framework material prepared in Example 1 of the present invention;

[0028] Figure 2 It is the X-ray diffraction spectrum of the copper-based metal organic framework material prepared in Example 1 and Comparative Example 1 of the present invention;

[0029] Figure 3 This is a comparison chart of infrared spectra of copper-based metal organic framework materials prepared in Example 1 of the present invention and Comparative Example 1;

[0030] Figure 4 is a scanning electron microscope image of the copper-based metal organic framework material prepared in Comparative Example 1 of the present invention;

[0031] Figure 5 is a scanning electron microscope image of the copper-based metal organic framework material prepared in Comparative Example 2 of the present invention;

[0032] Figure 6 is a scanning electron microscope image of the copper-based metal organic framework material prepared in Comparative Example 3 of the present invention;

[0033] Figure 7 is a scanning electron microscope image of the copper-based metal organic framework material prepared in Comparative Example 4 of the present invention;

[0034] Figure 8 This is a comparison diagram of linear voltammetric characteristic curves of the copper-based metal organic framework material prepared in Example 1 of the present invention and Comparative Example 1 for electrocatalytic reduction of carbon dioxide;

[0035] Fig. 9 The copper-based metal organic framework material prepared in Example 1 of the present invention is used for electrocatalytic reduction of carbon dioxide, and the current-time curve and ethylene Faraday efficiency-time curve are shown at a constant potential of -1.7 (V vs reversible hydrogen electrode). DETAILED DESCRIPTION

[0036] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0037] In one aspect, the present invention provides a copper-based metal organic framework material, wherein the metal organic framework material has a honeycomb spherical morphology;

[0038] The metal element in the metal organic framework material is copper;

[0039] The organic ligand in the metal organic framework material is trimesic acid;

[0040] Among them, the diameter of the spherical particles of the metal organic framework material is 0.8-8 microns.

[0041] In the metal organic framework material of the present invention, more than 80%, preferably more than 90% of the particles are spherical in shape.

[0042] It should be noted that the sphere described in the present invention may be a sphere in a narrow sense, or may be an incompletely regular sphere, such as a quasi-spherical shape.

[0043] The morphology of the metal organic framework material of the present invention is measured by a scanning electron microscope.

[0044] In the present invention, the diameter of the metal organic framework material spherical particles is 0.8-8 microns, preferably 1-5 microns. The metal organic framework material spherical particles of the present invention have a small diameter, which is conducive to promoting efficient mass transfer and active site exposure.

[0045] The diameter of the metal organic framework material of the present invention is obtained by observation through a scanning electron microscope.

[0046] The honeycomb spherical morphology of the metal organic framework material of the present invention refers to the metal organic framework material of the present invention being observed to have an overall spherical morphology under a scanning electron microscope, such as Figure 1 Figure b, then under the high magnification of the scanning electron microscope, it can be observed that the spherical particles have a layered porous structure that is evenly distributed and staggered, such as Figure 1 Figure a in the middle.

[0047] According to the present invention, preferably, the metal organic framework material has characteristic peaks at 2θ of 8.3°±0.2° and 17.0°±0.2° as characterized by X-ray diffraction.

[0048] It can be seen from the XRD spectrum that compared with the metal organic framework material of comparative example 1, the metal organic framework material of the present invention has characteristic peaks at 2θ of 8.3°±0.2° and 17.0°±0.2°. Figure 2 The use of such a metal organic framework material with a microstructure is beneficial to improving the Faraday efficiency of ethylene in the subsequent electrocatalytic reduction of carbon dioxide to ethylene reaction.

[0049] According to the present invention, preferably, the metal organic framework material is characterized by Fourier transform infrared spectroscopy at 1711±15cm -1 、1285±15cm -1 、1204±15cm -1 、1178±15cm-1 and 992±15cm -1 There are characteristic peaks.

[0050] It can be seen from the infrared spectrum that compared with the metal organic framework material of comparative example 1, the metal organic framework material of the present invention has a -1 、1285±15cm -1 、1204±15cm -1 、1178±15cm -1 and 992±15cm -1 There are characteristic peaks at Figure 3 This shows that the coordination environment of the metal organic framework material of the present invention changes during the preparation process, causing changes in the electronic structure of the metal active center, thereby achieving regulation of the adsorption intensity of different reaction intermediates and greatly improving the Faraday efficiency of ethylene.

[0051] According to the present invention, preferably, the metal organic framework material is formed by interweaving nanolayers.

[0052] It is understood that the honeycomb pores in the honeycomb spherical morphology of the metal organic framework material of the present invention are macropores formed by interweaving nanolayers, which can be referred to Figure 1 , which is beneficial to improve the mass transfer efficiency and thus enhance the catalytic activity.

[0053] According to the present invention, preferably, the thickness of the nanolayer is 10-80 nm, preferably 20-60 nm. This shows that the copper-based metal organic framework material of the present invention is interwoven by two-dimensional nanolayers. The layered two-dimensional surface greatly increases the exposure of active sites, further improving its catalytic activity.

[0054] The thickness of the nanolayer of the present invention is obtained by observation using a scanning electron microscope.

[0055] A second aspect of the present invention provides a method for preparing a copper-based metal organic framework material, the method comprising the following steps:

[0056] (1) mixing a methanol solution of a copper precursor with a methanol solution of trimesic acid to obtain a mixed solution; placing the mixed solution in a reaction container under a sealed condition to perform a hydrothermal reaction to obtain a solid product;

[0057] (2) washing and drying the solid product;

[0058] Wherein, the volume of the mixed solution is 18-50% of the volume of the reaction container;

[0059] The concentration of the copper precursor methanol solution is 40-100 mg / mL;

[0060] The concentration of the methanol solution of trimesic acid is 18-50 mg / mL.

[0061] In the preparation method provided by the present invention, a methanol solution of a copper precursor is used in combination with a methanol solution of trimesic acid, and the filling degree of the mixed solution in the reaction container and the concentration of the methanol solution of the copper precursor are controlled to prepare the copper-based metal organic framework material with a honeycomb spherical morphology as described in the above aspect of the present invention. The copper-based metal organic framework material of the present invention is conducive to improving the mass transfer efficiency, greatly improving its catalytic activity, and is applied to the electrocatalytic reduction of carbon dioxide to ethylene reaction, and has excellent stability and high ethylene Faraday efficiency.

[0062] The present invention has no particular limitation on the reaction vessel for the hydrothermal reaction in step (1), and it can be any reaction vessel that can realize the above hydrothermal reaction. The present invention uses a conventional hydrothermal reactor with a polytetrafluoroethylene liner as an example.

[0063] In the prior art, under the premise of ensuring the safety of the reaction, the volume of the mixed solution in the reaction container is generally as large as possible to obtain more metal organic framework materials. Usually, the volume of the mixed solution is 70-80% of the volume of the reaction container. In the present invention, the volume of the mixed solution is 18-50% of the volume of the reaction container, preferably 20-40%, for example, it can be 18%, 20%, 22%, 24%, 26%, 28%, 30%, 32%, 34%, 36%, 38%, 40%, 42%, 44%, 46%, 48%, 50%, and any value in the range formed by any two of these values. The use of this preferred embodiment is conducive to methanol vapor reducing the coordinated divalent copper nodes to cuprous, and forming a unique honeycomb spherical morphology and a new crystal structure after recrystallization.

[0064] In the present invention, the concentration of the methanol solution of the copper precursor is 40-100 mg / mL, preferably 40-60 mg / mL, for example, 40 mg / mL, 45 mg / mL, 50 mg / mL, 55 mg / mL, 60 mg / mL, 65 mg / mL, 70 mg / mL, 75 mg / mL, 80 mg / mL, 85 mg / mL, 90 mg / mL, 95 mg / mL, 100 mg / mL, and any value in the range formed by any two of these values. This preferred embodiment is advantageous for obtaining the copper-based metal organic framework material of the morphology and distribution described in the present invention.

[0065] According to the present invention, preferably, the concentration of the methanol solution of trimesic acid is 18-50mg / mL, preferably 20-30mg / mL. For example, it can be 18mg / mL, 20mg / mL, 22mg / mL, 24mg / mL, 26mg / mL, 28mg / mL, 30mg / mL, 32mg / mL, 34mg / mL, 36mg / mL, 38mg / mL, 40mg / mL, 42mg / mL, 44mg / mL, 46mg / mL, 48mg / mL, 50mg / mL, and any value in the range formed by any two of these numerical values. Adopting this preferred embodiment, it is conducive to obtaining the copper-based metal organic framework material of morphology and distribution described in the present invention.

[0066] According to the present invention, preferably, the mass ratio of the copper precursor to trimesic acid is 0.5-8.5, preferably 1-3.5, for example, it can be 0.5:1, 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1, 5.5:1, 6:1, 6.5:1, 7:1, 7.5:1, 8:1, 8.5:1, and any value in the range formed by any two of these values. The use of this preferred embodiment is more conducive to obtaining the copper-based metal organic framework material with the morphology and distribution described in the present invention.

[0067] In the present invention, the copper precursor can be a conventional choice in the art. Preferably, the copper precursor is selected from at least one of copper nitrate trihydrate, copper nitrate hexahydrate, copper sulfate, copper sulfate pentahydrate, copper sulfate hexahydrate, cupric chloride and cuprous chloride.

[0068] The present invention has no particular limitation on the mixing in step (1), and the mixing can be carried out according to conventional methods in the art.

[0069] According to the present invention, preferably, the conditions of the hydrothermal reaction in step (1) include: a temperature of 80-140°C, preferably 110-130°C, for example, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, and any value in the range formed by any two of these values; a time of 12-120h, preferably 18-84h, for example, 12h, 14h, 16h, 18h, 20h, 22h, 24h, 26h, 28h, 30h, 32h , 34h, 36h, 38h, 40h, 42h, 44h, 46h, 48h, 50h, 52h, 54h, 56h, 58h, 60h, 62h, 64h, 66h, 68h, 70h, 72h, 74h, 76h, 78h, 80h, 82h, 84h, 86h, 88h, 90h, 92h, 94h, 96h, 98h, 100h, 102h, 104h, 106h, 108h, 110h, 112h, 114h, 116h, 118h, 120h, and any value in the range formed by any two of these values. Adopting this preferred embodiment is conducive to improving the ethylene Faraday efficiency in the subsequent electrocatalytic reduction of carbon dioxide to produce ethylene.

[0070] Preferably, the method further comprises: performing solid-liquid separation on the product of the hydrothermal reaction in step (1) to obtain a solid product.

[0071] The present invention has no particular limitation on the method of solid-liquid separation, and the solid-liquid separation can be carried out by conventional technical means in the art.

[0072] The present invention has no particular limitation on the specific conditions of the washing, and the washing can be carried out according to methods in the art until the solution is clear.

[0073] The present invention has a wide range of choices for the type of detergent for washing, which can be a conventional choice in the art. Preferably, the detergent for washing is selected from at least one of water, methanol, ethanol and acetone.

[0074] The present invention has no particular limitation on the drying conditions of step (2), and the drying can be carried out according to methods in the art. Preferably, the drying is vacuum drying.

[0075] In the present invention, the solid product can be dried by taking all the material, or by taking part of the material from the surface of the solid product to the bottom. Preferably, in step (2), based on the depth of the solid product, materials within 40%, preferably 30%, of the depth of the solid product are taken from top to bottom along the surface of the solid product for drying. This preferred embodiment is further beneficial to improving the Faraday efficiency of ethylene in the subsequent electrocatalytic reduction of carbon dioxide to ethylene reaction.

[0076] It can be understood that in step (2), sampling is performed starting from the surface of the solid product downwards, and material within 40% of the depth of the solid product is sampled, that is, material within 40% of the depth from the surface of the solid product to the solid product can be sampled arbitrarily.

[0077] Preferably, the method does not include adding a structure regulator and / or a sacrificial template. By adopting this preferred embodiment, the preparation method provided by the present invention avoids the complicated process of adding an additional structure regulator or a sacrificial template commonly used in existing preparation methods, and has simple operation, mild preparation conditions, low cost, efficient synthesis method, easy scale-up, and good application advantages and prospects.

[0078] The structural regulator and / or sacrificial template agent of the present invention can be a conventional choice in the art, and the present invention will not be described in detail here.

[0079] The third aspect of the present invention provides an application of the copper-based metal organic framework material described in the first aspect or the copper-based metal organic framework material prepared by the preparation method described in the second aspect in the electrocatalytic reduction of carbon dioxide to produce ethylene.

[0080] The present invention has no particular limitation on the conditions for the electrocatalytic reduction of carbon dioxide to produce ethylene reaction, and the reaction can be carried out according to conventional methods in the art.

[0081] The present invention will be described in detail below through examples.

[0082] In the following examples, the detection method of the product is as follows:

[0083] Gas product analysis: A gas chromatograph (Agilent 7890B) was used, equipped with a hydrogen ion flame detector and a thermal conductivity detector. The thermal conductivity detector detected hydrogen, and carbon monoxide was detected by the hydrogen ion flame detector after hydrogenation in the methane reformer.

[0084] Liquid product analysis: Using hydrogen nuclear magnetic resonance (Agilent 700M), take the cathode electrolyte, add heavy water to lock the field, and use dimethyl sulfoxide as the internal standard.

[0085] Example 1

[0086] Take 0.721g of copper nitrate trihydrate and dissolve it in 17.5mL of methanol to prepare solution A; dissolve 0.352g of trimesic acid in 17.5mL of methanol to prepare solution B; mix solution A and solution B at room temperature and transfer them into a 100mL polytetrafluoroethylene-lined stainless steel-jacketed reactor, react at 120°C for 36h, and then cool to room temperature. Use a rubber-tipped dropper to remove the solvent in the reaction product of the hydrothermal reaction, and evaporate the residual solvent at room temperature to obtain a solid product. Take the material within 30% of the depth of the solid product from top to bottom along the surface of the solid product, wash it with ethanol, and then vacuum dry it at 80°C for 12h to obtain a copper-based metal organic framework material, recorded as HC-Cu-BTC.

[0087] The SEM image of the copper-based metal organic framework material described in Example 1 is given as an example. Figure 1 As shown. It can be seen that the copper-based metal organic framework material has a honeycomb spherical morphology, and the copper-based metal organic framework material is interwoven by nano layers. The thickness of the nano layer is about 30-50nm. The diameter of the metal organic framework material spherical particles is 1-5 microns.

[0088] The XRD pattern of the copper-based metal organic framework material described in Example 1 is given as an example. Figure 2 As shown. It can be seen that compared with Comparative Example 1, there are more diffraction peaks at 8.3 and 17.0°, indicating the formation of a new phase, and some of the Cu-BTC crystal phase prepared in Comparative Example 1 remains, corresponding to diffraction peaks at 9.6°, 11.8°, 13.5° and 19.2°. That is, compared with Comparative Example 1, the crystal structure of the copper-based metal organic framework material of the present invention has changed significantly.

[0089] The infrared spectrum of the copper-based metal organic framework material described in Example 1 is given as an example. Figure 3 As shown. It can be seen that compared with Comparative Example 1, at 1711cm -1 、1285cm -1 、1204cm -1 、1178cm -1 and 992cm -1 An obvious absorption peak appeared.

[0090] Example 2

[0091] Take 0.81g of copper nitrate trihydrate and dissolve it in 17.5mL of methanol to prepare solution A; dissolve 0.352g of trimesic acid in 17.5mL of methanol to prepare solution B; mix solution A and solution B at room temperature and transfer them into a 100mL polytetrafluoroethylene-lined stainless steel-jacketed reactor, react at 115°C for 72h, and then cool to room temperature. Use a rubber-tipped dropper to remove the solvent from the reaction product of the hydrothermal reaction, and evaporate the residual solvent at room temperature to obtain a solid product. Take the material within 30% of the depth of the solid product from top to bottom along the surface of the solid product, wash it with methanol, and then vacuum dry it at 80°C for 12h to obtain a copper-based metal organic framework material. The thickness of its nanolayer is 30-40nm. The diameter of the spherical particles of the metal organic framework material is 1.5-5 microns.

[0092] Example 3

[0093] Take 0.607g of copper nitrate hexahydrate and dissolve it in 12.5mL of methanol to prepare solution A; dissolve 0.392g of trimesic acid in 12.5mL of methanol to prepare solution B; mix solution A and solution B at room temperature and transfer them into a 100mL polytetrafluoroethylene-lined stainless steel-jacketed reactor, react at 125°C for 24h, and then cool to room temperature. Use a rubber-tipped dropper to remove the solvent from the reaction product of the hydrothermal reaction, and evaporate the residual solvent at room temperature to obtain a solid product. Take the material within 30% of the depth of the solid product from top to bottom along the surface of the solid product, wash it with deionized water, and then vacuum dry it at 80°C for 12h to obtain a copper-based metal organic framework material. The thickness of its nanolayer is 30-50nm. The diameter of the spherical particles of the metal organic framework material is 1-6 microns.

[0094] Example 4

[0095] The method of Example 1 is followed, except that the amount of copper nitrate trihydrate used is 1.750 g, to obtain a copper-based metal organic framework material, wherein the thickness of the nanolayer is 30-50 nm, and the diameter of the metal organic framework material spherical particles is 1-6 microns.

[0096] Example 5

[0097] The method of Example 1 is followed, except that the amount of trimesic acid used is 0.875 g, to obtain a copper-based metal organic framework material, wherein the thickness of the nanolayer is 30-50 nm, and the diameter of the metal organic framework material spherical particles is 1-6 microns.

[0098] Example 6

[0099] The method of Example 1 is followed, except that the hydrothermal reaction temperature is 140° C. to obtain a copper-based metal organic framework material, wherein the thickness of the nanolayer is 30-50 nm, and the diameter of the metal organic framework material spherical particles is 2-8 microns.

[0100] Example 7

[0101] The method of Example 1 is followed, except that the hydrothermal reaction time is 120 hours to obtain a copper-based metal organic framework material, wherein the thickness of the nanolayer is 30-50 nm, and the diameter of the metal organic framework material spherical particles is 2-8 microns.

[0102] Example 8

[0103] The method of Example 1 is followed, except that the material within 60% of the depth of the solid product is taken from top to bottom along the surface of the solid product, washed with ethanol, and then vacuum dried at 80° C. for 12 hours to obtain a copper-based metal organic framework material. The thickness of the nanolayer is 30-50 nm. The diameter of the spherical particles of the metal organic framework material is 0.8-6 microns.

[0104] Comparative Example 1

[0105] Copper-based metal organic framework material prepared by prior art

[0106] 2.952g of copper nitrate trihydrate was dissolved in 40.5mL of ethanol aqueous solution (ethanol: water volume ratio is 1:1) to prepare solution A; 1.713g of trimesic acid was dissolved in 40.5mL of ethanol aqueous solution (ethanol: water volume ratio is 1:1) to prepare solution B; solution A and solution B were mixed at room temperature and transferred into a 100mL polytetrafluoroethylene lined stainless steel jacket reactor, reacted at 120°C for 24h, and then cooled to room temperature. The reaction product of the hydrothermal reaction was separated to obtain a solid product.

[0107] The solid product was washed with ethanol, then soaked in ethanol for two days, with the ethanol replaced every 10 hours, and then vacuum dried at 80°C for 12 hours to obtain a classic octahedral bulk copper-based metal organic framework material, denoted as Cu-BTC.

[0108] The SEM image of the copper-based metal organic framework material described in Comparative Example 1 is as follows: Figure 4 As shown, the Cu-BTC is in the shape of a micron-sized octahedron.

[0109] The XRD pattern of the copper-based metal organic framework material described in Comparative Example 1 is as follows: Figure 2 As shown, it can be seen that it is consistent with the Cu-BTC crystal structure reported in existing literature.

[0110] The infrared spectrum of the copper-based metal organic framework material described in Comparative Example 1 is as follows: Figure 3 As shown in Figure 2, it can be seen that copper is fully coordinated with trimesic acid.

[0111] Comparative Example 2

[0112] The method of Example 1 was followed, except that the amount of methanol used to prepare the copper nitrate trihydrate solution was 7.5 mL, and the amount of methanol used to prepare the trimesic acid solution was 7.5 mL, to obtain a copper-based metal organic framework material.

[0113] The SEM image of the copper-based metal organic framework material described in Comparative Example 2 is as follows: Figure 5 As shown in Figure 2, it can be seen that the particles are mainly irregular blocks at the micron and nanometer scales.

[0114] Comparative Example 3

[0115] The method of Example 1 was followed, except that the amount of methanol used to prepare the copper nitrate trihydrate solution was 40 mL, and the amount of methanol used to prepare the trimesic acid solution was 40 mL, to obtain a copper-based metal organic framework material.

[0116] The SEM image of the copper-based metal organic framework material described in Comparative Example 3 is as follows: Figure 6 As shown, it can be seen that the morphology is uniform nanoparticles.

[0117] Comparative Example 4

[0118] The method of Example 1 was followed, except that 0.721 g of copper nitrate trihydrate was dissolved in 17.5 mL of ethanol to prepare solution A, and 0.352 g of trimesic acid was dissolved in 17.5 mL of ethanol to prepare solution B, to obtain a copper-based metal organic framework material.

[0119] The SEM image of the copper-based metal organic framework material described in Comparative Example 4 is as follows: Figure 7 As shown in Figure 2, it can be seen that its morphology is mainly micron-sized blocks.

[0120] Test Example 1

[0121] 5 mg of the copper-based metal organic framework material prepared in the embodiment and comparative example was dispersed in 500 μL of anhydrous ethanol, ultrasonicated for 15 min, 20 μL of perfluorosulfonic acid resin Nafion solution was added, ultrasonicated for 30 min to obtain a mixed solution, 60 μL of the mixed solution was drop-coated on 1 cm × 1 cm carbon paper, and it was left to stand for 0.5 hours at room temperature to dry, to obtain a working electrode loaded with copper-based metal organic framework material, wherein the loading of copper-based metal organic framework material was 0.58 mg. A 1 cm × 1 cm platinum sheet was used as a counter electrode, Ag / AgCl (saturated KCl) was used as a reference electrode, a proton exchange membrane (Nafion 117) separated the anode and cathode chambers, and selectively entered the cathode chamber through the anode cation, and a 0.1 M KHCO3 solution was used as an electrolyte, and an electrocatalytic carbon dioxide reduction test was performed in a three-electrode system H-type electrolytic cell composed of the above components. Pure carbon dioxide gas was used as the reactant, the gas mass flowmeter controlled the gas flow rate to be 30 mL / min, and the results of the reaction for 1 h at a potential of -1.7 (V vs reversible hydrogen electrode) are shown in Table 1.

[0122] Table 1

[0123]

[0124]

[0125] It can be seen from the results in Table 1 that the copper-based metal organic framework material provided by the present invention has a significantly higher ethylene Faraday efficiency when applied to the electrocatalytic carbon dioxide reduction reaction to produce ethylene.

[0126] At the same time, a comparison of the linear voltammetric characteristic curves of the copper-based metal organic framework material used in the electrocatalytic reduction of carbon dioxide to produce ethylene is given as an example. Figure 8 It can be seen that compared with the Cu-BTC in comparative example 1, at the same potential, the HC-Cu-BTC in example 1 can generate a larger current density, indicating that the HC-Cu-BTC in example 1 has a more excellent catalytic performance.

[0127] The HC-Cu-BTC prepared in Example 1 is used for the electrocatalytic reduction of carbon dioxide to produce ethylene, and the current-time curve and the ethylene Faraday efficiency-time diagram at a constant potential of -1.7 (V vs. reversible hydrogen electrode) are shown as follows: Fig. 9 As shown. It can be seen that within 24 hours of operation, the current density decreases slightly, and the Faraday of ethylene remains at the same level. It can be seen that the HC-Cu-BTC of Example 1 of the present invention has good stability.

[0128] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A copper-based metal organic framework material, characterized in that: The metal organic framework material has a honeycomb spherical morphology; The metal element in the metal organic framework material is copper; The organic ligand in the metal organic framework material is trimesic acid; Among them, the diameter of the spherical particles of the metal organic framework material is 0.8-8 microns.

2. The metal organic framework material according to claim 1, wherein Characterized by X-ray diffraction, the metal organic framework material has characteristic peaks at 2θ of 8.3°±0.2° and 17.0°±0.2°; And / or, the metal organic framework material is characterized by Fourier transform infrared spectroscopy at 1711±15cm -1 、1285±15cm -1 、1204±15cm -1 、1178±15cm -1 and 992±15cm -1 There are characteristic peaks.

3. The metal organic framework material according to claim 1 or 2, wherein: The metal organic framework material is formed by interweaving nanolayers; And / or, the thickness of the nanolayer is 10-80 nm, preferably 20-60 nm.

4. A method for preparing a copper-based metal organic framework material, the method comprising the following steps: (1) mixing a methanol solution of a copper precursor with a methanol solution of trimesic acid to obtain a mixed solution; placing the mixed solution in a reaction container under sealing conditions to perform a hydrothermal reaction to obtain a solid product; (2) washing and drying the solid product; Wherein, the volume of the mixed solution is 18-50% of the volume of the reaction container; The concentration of the copper precursor methanol solution is 40-100 mg / mL; The concentration of the methanol solution of trimesic acid is 18-50 mg / mL.

5. The method according to claim 4, wherein: The volume of the mixed solution is 20-40% of the volume of the reaction container; and / or, the concentration of the methanol solution of the copper precursor is 40-60 mg / mL; And / or, the concentration of the methanol solution of trimesic acid is 20-30 mg / mL.

6. The method according to claim 4, wherein: The mass ratio of the copper precursor to trimesic acid is 0.5-8.5, preferably 1-3.

5.

7. The method according to claim 4, wherein: The copper precursor is selected from at least one of copper nitrate trihydrate, copper nitrate hexahydrate, copper sulfate, copper sulfate pentahydrate, copper sulfate hexahydrate, cupric chloride and cuprous chloride.

8. The method according to any one of claims 4 to 7, wherein: The conditions of the hydrothermal reaction in step (1) include: temperature of 80-140° C., preferably 110-130° C.; time of 12-120 h, preferably 18-84 h.

9. The method according to any one of claims 4 to 7, wherein: In step (2), based on the depth of the solid product, materials within 40%, preferably 30%, of the depth of the solid product are taken from top to bottom along the surface of the solid product for drying.

10. Use of the copper-based metal organic framework material according to any one of claims 1 to 3 or the copper-based metal organic framework material prepared by the preparation method according to any one of claims 4 to 9 in the electrocatalytic reduction of carbon dioxide to produce ethylene.

Citation Information

Patent Citations

  • Spherical forming Cu base metal organic skeleton-graphene oxide composite material and preparation method of spherical forming Cu base metal organic skeleton-graphene oxide composite material

    CN104226256A

  • Preparation method of modified metal-organic framework material and material prepared by same

    CN109734957A

  • Preparation method and application of copper metal organic framework composite material

    CN113578271A